"مشکوٰۃ المصابیح "پر شیخ عبدالحق محدث دہلوی کے کام کا جائزہ: Review of the work of Sheikh Abdul Haq Mohaddith Dehlavi on "Mishkāt al-Maṣābīḥ" - Faisal Qureshi, Muhammad; Fazal Haq, Muhammad (Al-Amīr Research Journal for Islamic Studies, 2021)
"Mishkāt al-Maṣābīḥ" has a sound rank among the Hadith collections. Its importance can be gauged from the fact that it has been described and summarized by several scholars. The works of Sheikh Abdul Haq Muḥaddith Dehlavi over that is a great contribution and have a special place in the context of his Hadith services. He is one of the prominent muhaddithin of the Subcontinent. He was pioneer in teaching and disseminating Hadith knowledge in the subcontinent. Firstly, he described the Mishkāt al-Maṣābīḥ in the Persian language of that time, which gained immense popularity among the people and increased the taste for understanding Hadith. Secondly, He accumulated a treasure trove of mysteries and secrets in Arabic for the use of Researchers. The name of the Persian commentary is Ash‘atul Lam‘āt while the Arabic commentary is called Lam‘āt al-Tanqīh. They are more than one in usefulness, which has created a taste for reading and understanding Hadith among the people and Researchers. In the said article, an introduction and methodological study of the work done by Sheikh Abdul Haq on Mishkāt al-Maṣābīḥ will be presented.